Double check up of malignancy biopsy specimens for patient safety - Pattana Sornmayura (2018)
Background: The diagnostic of malignancy in biopsy specimens is very important because it guides to selected treatment option and prognostic prediction. However, biopsy specimens usually have small pieces leading to variations of the interpretation by anatomical pathologists. Objective: To detect and correct the errors or the significant discrepancies in the diagnosis of biopsy specimens before signout and to determine the frequency of anatomic pathology significant discrepancies. Design: The application of the mutually agreed work instructions (record) for the detection of errors or the significant discrepancies and their process of sign-out. The record of biopsy specimen that received a secondary check (1,959 cases, 2005-2007) was analyzed. Results: After a secondary check, 53 cases of non-malignancy for any reason by a second pathologist were included. However, when using our definition on significant discrepancies, only 37 cases were considered. Another seven cases with the opinions with malignancy that were of different cell types that do harm to the patients were added. Therefore, 44 cases (2.25%) had truly significant discrepancies. Conclusion: The truly significant discrepancy frequency was 2.25% during the process of pre-sign-out secondary check of malignancy of biopsy specimens. The project has been applied as a routine daily work. It can be an innovative safety program for patient in Thailand.